2021
DOI: 10.1017/dmp.2021.269
|View full text |Cite
|
Sign up to set email alerts
|

Staffing in a Level 1 Trauma Center: Quantifying Capacity for Preparedness

Abstract: Objective: We sought to determine who is involved in the care of a trauma patient. Methods: We recorded hospital personnel involved in 24 adult Priority 1 trauma patient admissions for 12 h or until patient demise. Hospital personnel were delineated by professional background and role. Results: We cataloged 19 males and 5 females with a median age of 50-y-old (interquartile range [IQR], 35.5-67.5). The average number of hospital personnel involved was 79.71 (standard de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Prompt completion of accurate secondary/tertiary surveys, early initiation of rehabilitation and provision of comprehensive nutrition, pain relief and clinical psychology support are key indicators of their performance ( 96 ). In 2022, a US study reported that each severely injured patient requires on average input from approximately 80 healthcare clinicians upon their arrival to a hospital ( 97 ). This is indicative of the complexity of their problems and the magnitude of resources that need to be readily available in an MTC.…”
Section: Key Elements Of the Trauma Ward Carementioning
confidence: 99%
“…Prompt completion of accurate secondary/tertiary surveys, early initiation of rehabilitation and provision of comprehensive nutrition, pain relief and clinical psychology support are key indicators of their performance ( 96 ). In 2022, a US study reported that each severely injured patient requires on average input from approximately 80 healthcare clinicians upon their arrival to a hospital ( 97 ). This is indicative of the complexity of their problems and the magnitude of resources that need to be readily available in an MTC.…”
Section: Key Elements Of the Trauma Ward Carementioning
confidence: 99%